Producing artifact-free projection overlaps with baffles - Lin, Jianyu (Institute of Electrical and Electronics Engineers Inc., 2013)
In multi-pinhole SPECT, overlapping the projections from different pinholes has been used to increase sensitivity. However, the prevailing view is that the overall quality of the reconstructed image is not improved by the projection overlaps because of the associated artifacts. On the other hand, contrary to the prevailing view, some recent studies show that artifact-free projection overlaps do exist, and that artifact-free overlaps do contribute to the final quality of the reconstructed images. In our previous paper [2], two types of artifact-free overlaps are formally defined and theoretically proved. However, one problem of applying the type-II artifact-free overlap to produce axially aligned overlaps in pinhole imaging system design is that the principle requires to image and reconstruct the entire object. In this work, a new proposition is introduced to relax this requirement. Satisfying the new requirement, one can make use of baffles to design axially overlapping pinhole imaging systems that only image a portion of the object and recover a fractional region of interest without any artifact.